2022
DOI: 10.1371/journal.pone.0270309
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals regulation mechanism of methyl jasmonate-induced terpenes biosynthesis in Curcuma wenyujin

Abstract: Curcuma wenyujin is the source plant of three traditional Chinese medicines, which have been widely used in clinical treatment over 1000 years. The content of terpenes, the major medicinal active ingredients, is relatively low in this plant. Studies have shown that MeJA can promote terpenes biosynthesis in plants. However, the mechanism underlying the effect of MeJA in C. wenyujin remains unclear. In this work, the transcriptome of C. wenyujin leaves with MeJA treatment was analyzed to elucidate the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Increasing evidence has shown that JA synthesis-related genes, e.g., DXS , DXR and OPR3 in P. quinquefolius and Solanum tuberosum L. upregulate their expression levels in response to the induction of R. intraradices and R. irregularis ( Schoenherr et al., 2019 ; Ran et al., 2021b and 2023 ). Wei et al. (2022) confirmed that in Curcuma wenyujin Y. Chen & C. Ling, the expression levels of key enzyme-encoding genes ( LOX , AOS , AOC , OPR , MFP and JAR ) involved in JA biosynthesis and JA signal transduction genes ( MYC2 and JAZ ) increased significantly under MeJA.…”
Section: Discussionsupporting
confidence: 65%
“…Increasing evidence has shown that JA synthesis-related genes, e.g., DXS , DXR and OPR3 in P. quinquefolius and Solanum tuberosum L. upregulate their expression levels in response to the induction of R. intraradices and R. irregularis ( Schoenherr et al., 2019 ; Ran et al., 2021b and 2023 ). Wei et al. (2022) confirmed that in Curcuma wenyujin Y. Chen & C. Ling, the expression levels of key enzyme-encoding genes ( LOX , AOS , AOC , OPR , MFP and JAR ) involved in JA biosynthesis and JA signal transduction genes ( MYC2 and JAZ ) increased significantly under MeJA.…”
Section: Discussionsupporting
confidence: 65%
“…MeJA induces both the production of MVA- and MEP pathway-derived metabolites [ 22 , 42 , 43 ]. With this in mind, we hypothesized that MeJA may affect the metabolic flux leading to the biosynthesis of prenyl diphosphates used to modify proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that the expression levels of key enzyme genes ( DXS , DXR , MCT , MCS , and HDS ) for skeleton synthesis were up-regulated under the action of MeJA, which is similar to the studies in Chrysanthemum indicum var. aromaticum [ 61 ], Curcuma wenyujin [ 64 ], and Artemisia annua [ 60 ], indicating that the synthesis of monoterpenoid in S. tenuifolia is mediated by the MEP pathway. In addition, we identified two HDR genes in S. tenuifolia , and the researchers showed that HDR was highly expressed in Artemisia annua [ 57 ] and Salvia miltiorrhiza [ 65 ] after MeJA treatment, but we found that the expression levels of StHDR after MeJA treatment were significantly down-regulated compared with the CK group, and the specific molecular mechanism needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%